2022
DOI: 10.1371/journal.pone.0265662
|View full text |Cite|
|
Sign up to set email alerts
|

Vegan versus meat-based dog food: Guardian-reported indicators of health

Abstract: Alternative pet foods may offer benefits concerning environmental sustainability and the welfare of animals processed into pet foods. However, some worry these may compromise the welfare of pets. We asked 2,639 dog guardians about one dog living with them, for at least one year. Among 2,596 involved in pet diet decision-making, pet health was a key factor when choosing diets. 2,536 provided information relating to a single dog, fed a conventional meat (1,370 = 54%), raw meat (830 = 33%) or vegan (336 = 13%) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(81 citation statements)
references
References 43 publications
(58 reference statements)
5
74
2
Order By: Relevance
“…Details of the final dataset used for statistical analysis are shown in Table 1 and were similar to the data used in the previous study [15]. Briefly, owners represented a broad age range, with a relatively even distribution in education level, from high school to postgraduate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the final dataset used for statistical analysis are shown in Table 1 and were similar to the data used in the previous study [15]. Briefly, owners represented a broad age range, with a relatively even distribution in education level, from high school to postgraduate.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, two binary variables were created, an any health problem variable and a significant illness variable, which could then be separately be assessed by binary logistic regression and machine learning predictive modelling, as described below. 1 Definitions of the different categories are given in the original study [15]. 2 Please see the footnote to Table 1 for details of how owner and dog diets were assigned.…”
Section: Variables Associated With Owner-reported Illness Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the COVID-19 pandemic has not had a large detrimental influence on the market for plant-based pet food, while the demand for plant-based pet food online shopping increased significantly ( Figure 1 ) ( 22 ). Based on research conducted by Insight Partners, the global market for plant-based pet food production is expected to increase from nearly US$8.6 billion in 2021 to almost US$15.6 billion by 2028, which clearly indicates the huge investment in this area ( 23 ).…”
Section: Plant-based Pet Food Status In the Post-covid-19 Pandemic Eramentioning
confidence: 99%
“…In a recent paper (Knight and others 2022) 336 guardians feeding vegan diets participated in a global online survey and the authors concluded that, “when compared to conventional meat-based or raw meat rations the healthiest and least hazardous dietary choices for dogs, are nutritionally sound vegan diets”. In this study some health issues were mentioned but there were no data on specific changes in health status following a switch to feeding vegan.…”
Section: Introductionmentioning
confidence: 99%